Prevalence of hypertension and its associated factors among tribal population in Southern Rajasthan - Nitesh Mangal; Matariswa Samanta; Patel, Mehul; Dilip Kumar L; Varghese KA; Mansi Sharma (Asian Journal of Medical Sciences, 2022)
Background: The prevalence of hypertension (HTN) and associated factors across social groups including tribal communities as a major non-communicable disease across world is a topic of very high contemporary relevance, especially when it is misconceived as a cause of morbidity only for the richer strata of the society. Aims and Objectives: The present study was conducted to assess the prevalence of HTN and its associated factors among tribal population in South Rajasthan. Materials and Methods: The cross-sectional study is based on a sample of 300 adult members living in 160 randomly selected tribal households in Udaipur district.The information collected included systolic and diastolic blood pressure along with a set of associated sociodemographic, behavioral risk factors, level of physical activities, and body mass index. The descriptive statistical measures such as class frequencies, mean, standard deviation, and Chi-square test of significance for association were used. Results: The estimated overall prevalence of HTN was 23.33% with 29.05% for male and 17.76% for female tribal adult population. The sex, age,family history of HTN, occupation, socioeconomic class, and landholding size were found significantly associated with HTN.The risk factors such as alcohol consumption, smoking, and additional salt intake emerged with odds ratio of 1.83, 2.94, and 1.14, respectively. Conclusion: The health intervention focused to increase physical activity and to reduce alcohol consumption, smoking, and additional salt intake can prove to be effective control measures for emerging problem of HTN in tribal area.